Variation Characteristics of Surface Wind Speed and Gale Events in the South China Sea from 1979 to 2021 - Chenxuan LI; Zhigang WEI (Gaoyuan qixiang, 2024)
In this paper， the gale events are defined firstly.Using ERA5 reanalysis data， the variation characteristics of the sea surface wind speed and the gale events from 1979 to 2021 were analyzed.The variation characteristics of sea surface wind speed and gale event in the South China Sea from 1979 to 2021 were analyzed using methods such as the empirical orthogonal decomposition.Specifically， the effects of tropical cyclones were distinguished.The results show that the distribution of wind speed in the South China Sea has obvious seasonal characteristics with the northeast wind in winter and in the summer， the wind direction turns to be southwest.Except for the northeast coastal areas， the mean wind speed in the spring time experienced a decreasing-increasing-decreasing character.While in the summer， it turns to a kind of increased-decreasing-increasing trend and the overall trend is decreasing.The consistent change of wind speed in the whole area of the South China Sea in the autumn shows a decreasing trend.In the winter， the wind speed in the southeast of the South China Sea is opposite to the rest aera， with a significant increase in wind speed except for the southwest.The frequency of the gale events that occur in the winter and in the autumn is higher than that in the spring and autumn， and the frequency of the gale events in the winter half year is higher than that in the summer half year.In the winter or winter half year， the frequency of the gale event has a significant increasing trend， especially in the area from the east of the Annamese Cordillera to area near the Taiwan Strait， through the central part of the South China Sea， in the northeast part of the South China Sea.The variation trend of the frequency of gale event in the winter and spring is opposite to that in the summer and autumn.The changes of the frequency of gale event in the summer half year combines the characteristics of the variation trends in the summer and autumn.Similarly， gale event that occur in the winter half year combines the variation trends of winter and spring.During the seasons affected by the South China Sea summer monsoon， such as summer， autumn， and the summer half year， tropical cyclones have a greater impact on the frequency of gale event which is different from the gale event that appearance in the winter， spring and winter half year.